The Future Rôle of Western Missionary Bodies in the Christian World Mission - Orchard, Ronald K. (International review of mission, 1969)
This article appeared in Voyage, No. 11, Sept./Oct. 1968, the periodical of the British Council of Churches. It is used with permission of the editor, to whom our thanks are expressed. It is based on the conclusions of a residential meeting of the Standing Committee of the Conference of British Missionary Societies, June 1968, which gathered up several months of discussion in the CBMS.